The Analysis Influence of Brand Image, Brand Awareness and Brand Trust On Decisions Using Delivery Services PT ID Express Central Java - Thutur - Pangestu; Suwardi - Suwardi; Suryadi - Poerbo (Admisi dan Bisnis, 2021)
This study aims to determine the effect of brand image, brand awareness and brand trust on the decision to use the delivery service of PT ID Express Central Java. Data collection methods used in the study were observation, questionnaires and literature studies. The questionnaire scale in this study used a Differential Semantic Scale with the form of the scoring technique carried out in this study was a minimum of 1 and a maximum of 10. The sample in this study was 100 consumers of PT ID Express Central Java who were selected using the accidental sampling technique. The data analysis technique used was multiple linear regression. The results show that partially or simultaneously brand image, brand awareness, brand trust had a significant positive effect on the decision to use the delivery service of PT ID Express Central Java with an influence contribution of 56%. This means that in improving the decision to use services for consumers, it is necessary to increase brand associations, especially the formation of a positive brand image, increase brand awareness through effective marketing management, and memorable services in order to create high confidence in the company's brand.